SMART CONTRACT TECHNIQUE TO BUILD DATA AGGREGATION FRAMEWORK ON LARGE SCALE IOT SYSTEMS (International Journal of Food and Nutritional Sciences, 2019)
Building scalable and secure Industrial IoT (IIoT) system is the need of the hour in Industrial4.0. However, existing IIoT systems are vulnerable to a single point of failure and maliciousattacks. To address the security and efficiency issues of the massive IIoT data, blockchain iswidely considered as a promising solution to enable data storing, processing, and sharing in asecure and efficient way